Design, synthesis and antibacterial evaluation of pleuromutilin derivatives. (1st April 2022) - Wu, Guangxu; Zhu, Zihao; Li, Jishun; Luo, Xinyu; Zhu, Wenyong; Liao, Guoyang; Xia, Jie; Zhang, Wenxuan; Pan, Weidong; Li, Tianlei; Wu, Song
Graphical abstract: We report herein the design, synthesis, and structure-activity relationship studies of pleuromutilin derivatives containing urea/thiourea functionalities. The antibacterial activities of these new pleuromutilin derivatives were evaluated in vitro against Gram-positive pathogens (GPPs) ( Staphylococcus aureus, Staphylococcus epidermidis, and Enterococcus faecium ) and Mycoplasma pneumoniae by the broth dilution method. Most of the targeted compounds exhibit good potency in inhibiting the growth of pathogens including Methicillin-susceptible S. aureus (MSSA, ATCC29213, MIC: 0.0625–16 μg/mL), Methicillin-resistant S. aureus (MRSA, ATCC43300, MIC: 0.125–16 μg/mL) and M. pneumoniae (ATCC15531 MIC: 0.125–1 μg/mL, ATCC29342 MIC: 0.0625–0.25 μg/mL, and drug resistant strain MIC: 0.5–2 μg/mL). In particular, the compounds 6m and 6n containing phenyl-urea group showed excellent activity with the MIC value less than 0.0625 μg/mL against S. aureus ATCC29213. The compound 6h exhibited better activity than tiamulin against Methicillin-resistant S. aureus ATCC43300. Abstract: We report herein the design, synthesis, and structure-activity relationship studies of pleuromutilin derivatives containing urea/thiourea functionalities. The antibacterial activities of these new pleuromutilin derivatives were evaluated in vitro against Gram-positive pathogens (GPPs) ( Staphylococcus aureus, Staphylococcus epidermidis and Enterococcus faecium ) and Mycoplasma pneumoniae by the broth dilution method. Most of the targeted compounds exhibit good potency in inhibiting the growth of pathogens including Methicillin-susceptible S. aureus (MSSA, ATCC29213, MIC: 0.0625–16 μg/mL), Methicillin-resistant S. aureus (MRSA, ATCC43300, MIC: 0.125–16 μg/mL) and M. pneumoniae (ATCC15531 MIC: 0.125–1 μg/mL, ATCC29342 MIC: 0.0625–0.25 μg/mL and drug resistant strain MIC: 0.5–2 μg/mL). In particular, the compounds 6 m and 6n containing phenyl-urea group showed excellent activity with the MIC value less than 0.0625 μg/mL against S. aureus ATCC29213. The compound 6 h exhibited better activity than tiamulin against Methicillin-resistant S. aureus ATCC43300.